2001
DOI: 10.1080/03005364.2001.11742728
|View full text |Cite
|
Sign up to set email alerts
|

A study of the application of a frequency transposition hearing system in children

Abstract: The aim of this retrospective study was to investigate the use of the frequency transposition Transonic FT 40 system in a group of 36 children with profound sensorineural hearing loss. The group comprised 36 children (11 boys, 25 girls) aged between 2.8 and 15.6 years (mean 7.6 years) at fitting of the FT 40 device. At 48 months post-FT 40 fitting, only 11 children (30%) were still wearing the device. The children discontinued wearing the FT 40 for the following reasons: ergonomic (11%); no perceived benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Briefly, the majority of these studies were conducted utilizing a frequency compression hearing aid that operated by compressing the whole spectrum by a fixed ratio once a decision on ''voiced'' versus ''voiceless'' sounds was made. The results of these studies showed a lackluster effect of frequency compression (Parent et al, 1998;McDermott and Dean, 2000;McDermott and Knight, 2001;MacArdle et al, 2001). The only exception was the Miller-Hansen et al's (2003) retrospective review where the performance with frequency compression was compared to that of the subjects' own hearing aids.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Briefly, the majority of these studies were conducted utilizing a frequency compression hearing aid that operated by compressing the whole spectrum by a fixed ratio once a decision on ''voiced'' versus ''voiceless'' sounds was made. The results of these studies showed a lackluster effect of frequency compression (Parent et al, 1998;McDermott and Dean, 2000;McDermott and Knight, 2001;MacArdle et al, 2001). The only exception was the Miller-Hansen et al's (2003) retrospective review where the performance with frequency compression was compared to that of the subjects' own hearing aids.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…This type of approach has produced mixed results, with some studies showing substantial improvement and others showing no improvement or degradation in performance. [23][24][25][26] However, the signal-processing schemes across studies have differed substantially in concept and implementation. In addition, some studies included subjects who clearly were not candidates for this type of technology.…”
Section: Limited Bandwidth Of Hearing Aids: Potential Solutionsmentioning
confidence: 99%
“…above 2.5 kHz). Early studies indicated mixed outcomes with the body-worn FT-40 on adults and children, concluding that the FT-40 system was suitable for a select group of listeners (MacArdle et al, 2001; Parent et al, 1997). AVR Sonovations later introduced the ImpaCt behind-the-ear (BTE) hearing aid.…”
mentioning
confidence: 99%